2014
DOI: 10.1890/13-1445.1
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐mediated environmental filtering drives assembly at biogeographic transition zones

Abstract: Abiotic filtering is a major driver of gradients in the structure and functioning of ecosystems from the tropics to the poles. It is thus likely that environmental filtering is an important assembly process at the transition of biogeographical zones where many species occur at their range limits. Shifts in species abundances and association patterns along environmental gradients can be indicative of environmental filtering, which is predicted to be stronger in areas of high abiotic stress and to promote increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
157
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 58 publications
6
157
1
1
Order By: Relevance
“…Golbuu et al, 2016), reduced pH has been shown to limit the abundance (Price et al, 2012) and diversity (Fabricius et al, 2011;Crook et al, 2012) of calcifying organisms at other locations. In the present study, pH at the seagrass sites routinely dropped to values considered unfavorable for most corals (e.g., <7.8, Figure 2; see also Camp et al, 2016a), and therefore may have resulted in environmental filtering against some coral species (Sommer et al, 2014). The ability to tolerate reduced pH varies among coral species (McCulloch et al, 2012), and importantly, low pH appears to inhibit settlement of Acropora palmata, potentially through alteration of larval settlement processes or chemical settlement cues from crustose coralline algae (Albright et al, 2010).…”
Section: Physicochemical Conditionsmentioning
confidence: 53%
“…Golbuu et al, 2016), reduced pH has been shown to limit the abundance (Price et al, 2012) and diversity (Fabricius et al, 2011;Crook et al, 2012) of calcifying organisms at other locations. In the present study, pH at the seagrass sites routinely dropped to values considered unfavorable for most corals (e.g., <7.8, Figure 2; see also Camp et al, 2016a), and therefore may have resulted in environmental filtering against some coral species (Sommer et al, 2014). The ability to tolerate reduced pH varies among coral species (McCulloch et al, 2012), and importantly, low pH appears to inhibit settlement of Acropora palmata, potentially through alteration of larval settlement processes or chemical settlement cues from crustose coralline algae (Albright et al, 2010).…”
Section: Physicochemical Conditionsmentioning
confidence: 53%
“…In nature, community assembly may result from several interacting factors like species—environment relationships together with stochastic dispersal and demographic processes [9]. Chase [6] suggested from experiments that the relative importance of dispersal and niche processes will depend on the harshness of the environmental filter, and the interaction between the environment and dispersal may also be influenced by species functions or ecological traits [7, 10]. For instance, differences in dispersivity traits were of major importance for community assembly in metacommunities [11, 12], which by definition are communities connected by dispersal [4].…”
Section: Introductionmentioning
confidence: 99%
“…Low temperatures, low light availability and high attenuation in winter, low aragonite saturation and high competition with seaweeds are pervasive stressors for corals in these environments (Miller, 1995;Miller and Hay, 1996;Kleypas et al, 1999;Sommer et al, 2017). These stressors filter species so that high latitude coral communities are largely dominated by corals which are generalists with broad niche requirements (Sommer et al, 2014;Keith et al, 2015;Mizerek et al, 2016). The stress tolerant nature of most high latitude species could thus explain the low impact of the 2016 MCS.…”
Section: Discussionmentioning
confidence: 99%
“…These species are largely generalists with broad niche requirements (Sommer et al, 2014;Keith et al, 2015;Mizerek et al, 2016), and they regularly experience temperatures that are considered "cold" (<18 • C), for these inherently tropical taxa (Veron, 1995). Although resilient, these corals are not impervious to the stressful conditions at high latitudes.…”
Section: Introductionmentioning
confidence: 99%